PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN INSTALASI PENJAMINAN RSUP DR. SARDJITO YOGYAKARTA - ARY ESTININGSIH (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aimed to explain the influence of the partial work motivation on employee performance, toexplain the influence of the partial work environment on employee performance and to explain work motivation and work environment on employee performance simultaneously. The research method involves two variables : the independent variabel (employee performance), and the dependent variables (work motivation, work environment). The population of this research are 53 empoyess on Guarantee Instalation. The sample size ie 47 respondent. The sampling method used is sampling accidental. The data are analyzed using multiple linier regression. Based on the results of the analysis indicate that the work motivation is significantly influence the performance of the employees of Guarantee Instalation RSUP Dr. Sarjito Yogyakarta, indicated by the t significant value of 0,000 smaller than α =0,05 (0,000 < 0,05) with the regression coefficient of 0,355.Work environment has a significant effect on the performance of employees of Guarantee Instalation RSUP Dr. Sarjito Yogyakarta, indicated by the t significant value of 0,000 less than α = 0,05 (0,000 < 0,05) with the regression coefficient of 0,342. Work motivation and the work environment is simultaneously significant effecting the performance of employees in Guarante Instalasi RSUP Dr. Sarjito Yogyakarta, indicated by F significant value of 0,000 smaller than α = 0,05 (0,000 <0,05) and were able to contribute to the performance variables of 0,616 or 61,6 %. The remaining 38,4 %is influenced by other variables that are not examined in this study.